THE INFLUENCE OF COLLABORATIVE STRATEGIC READING (CSR) AND READING ATTITUDE TOWARD READING COMPREHENSION ACHIEVEMENT TO THE TENTH GRADE STUDENTS OF SMA NEGERI 1 BUAY MADANG OKU TIMUR - Eka Agustina (Channing : Journal of English Language Education and Literature, 2016)
This study aimed at finding out whether or not Collaborative Strategic Reading (CSR) and studentsâ€™ reading attitude influence the studentsâ€™ reading comprehension and there was or no a significant interaction effect of Collaborative Strategic Reading (CSR) and studentsâ€™ reading attitude toward the tenth grade studentsâ€™ reading comprehension of SMA Negeri 1 Buay Madang OKU Timur. The population of this study was 131 students of SMA Negeri 1 Buay Madang OKU Timur. From the population, there were 40 students taken as sample of experimental group and 40 students were as control group. The sample was taken using stratified random sampling. In carrying out the research, the writer used a factorial group design. Finnaly the calculation using a two-way ANOVA was used to measure an interaction between Collaborative Strategic Reading (CSR) and students reading attitude on their reading comprehension. Test of Between-Subjects Effects analyses, the significant value of the techniques (CSR and traditional) and the studentsâ€™ reading attitude were 0.130, the probability sig. of technique was 0.175, and the interaction between positive and negative attitude was 0.245 which higher than the significant level of p-value 0.05, it meant that there was no a significant interactions between studentsâ€™ interest and techniques. So, the research hypothesis that stated â€œthere is no an interaction between CSR and reading attitude toward studentsâ€™ reading comprehensionâ€ was accepted and the null hypothesis was not rejected based on the data finding.